Hydrogen detection element and hydrogen detection device
By employing an electromagnetic metamaterial with a metastructure of hydrogen storage metal films arranged at a pitch of 1,000 nm or less, the hydrogen detection element achieves improved response speed and reduced costs, facilitating accurate hydrogen detection using visible light to near-infrared light without precious metals.
Patent Information
- Application Number
- JP2023163552
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-08
AI Technical Summary
Conventional hydrogen detection technologies using electromagnetic metamaterials face challenges in improving hydrogen storage time (response speed) and cost, often requiring precious metals and specialized spectrometers.
The development of a hydrogen detection element featuring an electromagnetic metamaterial with a metastructure of hydrogen storage metal films arranged periodically at a pitch of 1,000 nm or less, which controls the reflection, transmission, or absorption spectrum of incident electromagnetic waves, allowing for detection using visible light to near-infrared light without precious metals.
This approach enhances hydrogen storage time (response speed) while reducing costs, enabling accurate hydrogen detection using low-cost spectrometers and eliminating the need for precious metals.
Smart Images

Figure 2025054489000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogen detection element and a hydrogen detection device. [Background technology]
[0002] In recent years, the use of hydrogen as a new energy source that does not emit carbon dioxide has been attracting attention, and the market is expected to expand worldwide. However, the hydrogen-related industry is hindered by safety issues due to the fact that hydrogen is a flammable gas and low social awareness of hydrogen, as well as price issues due to the fact that the environment for using hydrogen is still in its infancy and hydrogen itself is expensive. One solution is the development of highly accurate, safe, and inexpensive hydrogen detection technology.
[0003] Conventional hydrogen detection methods have often used catalytic combustion or semiconductor methods. However, these methods have the disadvantage that the presence of electrical contacts in the sensor section poses the risk of fire, making explosion prevention measures necessary, and that the need for heating consumes a lot of power, necessitating the installation of wired connections. Therefore, research is being conducted on a hydrogen detection method in which the sensor section is entirely made up of optical systems, which does not have the above-mentioned disadvantages, is highly safe, and does not require heating.
[0004] For example, Patent Document 1 describes a technology for detecting hydrogen by using a hydrogen-sensitive switchable mirror to detect changes in light reflectance and transmittance that accompany hydrogenation. Patent Document 2 describes a technology for detecting hydrogen by using a surface plasmon resonance element made of an electromagnetic metamaterial configured by forming periodic openings in a thin film of palladium (Pd), a hydrogen storage metal, to detect changes in optical frequency characteristics that accompany hydrogen storage. Patent Document 3 also describes a technology for configuring an electromagnetic metamaterial from palladium and detecting hydrogen from the spectrum change before and after hydrogen storage.
[0005] Electromagnetic metamaterials are a technology that can precisely control the absorption, transmission, and reflection of electromagnetic waves by using a microstructure in which meta-structures called meta-atoms and meta-molecules are arranged at a specified pitch. A periodic structure smaller than the wavelength of the electromagnetic wave to be used is created with a metal (or a material with a negative dielectric constant), and the transmission and reflection of electromagnetic waves of any wavelength can be controlled by surface plasmon resonance. Furthermore, the property changes greatly depending on the refractive index of the metal used. Figure 1 is a conceptual diagram of a hydrogen detection element using electromagnetic metamaterials. When a hydrogen-storing metal such as Pd is used as the metal for use in electromagnetic metamaterials, the refractive index changes when hydrogen is absorbed into Pd in the presence of hydrogen, and the surface plasmon resonance wavelength (absorption peak wavelength) shifts (from 860 nm to 930 nm in the example of Figure 1), making it possible to detect the presence of hydrogen. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2005-265590 A [Patent Document 2] International Publication No. 2011 / 027899 [Patent Document 3] Patent No. 6775236 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in conventional hydrogen detection technology using electromagnetic metamaterials, the recognition of the problem of improving hydrogen absorption time (response speed) is not necessarily sufficient, as shown in Patent Document 2. In Patent Document 3, it is necessary to mix precious metals such as gold with the hydrogen absorption metal to improve the response speed, which has the problem of increasing the number of manufacturing steps and making the sensor expensive. Furthermore, the wavelength of the electromagnetic waves used is about 3 to 6 μm, and a special spectroscope is required to detect this, which is thought to make the sensor itself expensive.
[0008] The present invention has been made in consideration of the above points, and has an object to provide a technique for improving the hydrogen absorption time (response speed) while suppressing costs in a hydrogen detection element. [Means for solving the problem]
[0009] In order to solve the above problems, one representative hydrogen detection element of the present invention is an electromagnetic metamaterial in which metastructures of a specified shape and size made of a hydrogen-absorbing metal film are periodically arranged on a substrate at a specified pitch, the pitch being 1,000 nm or less, and which controls the reflection, transmission, or absorption spectrum of incident electromagnetic waves. Effect of the Invention
[0010] According to the present invention, it is possible to improve the hydrogen absorption time (response speed) of a hydrogen detection element while suppressing costs. For example, it is possible to provide a hydrogen detection element that has a hydrogen absorption time (response speed) of the order of 10 seconds without blending a precious metal into the hydrogen storage metal, and that can detect hydrogen with high accuracy using detection light in the wavelength range from visible light to near-infrared light that can be measured with an inexpensive spectrometer. Problems, configurations and effects other than those described above will become apparent from the description of the following embodiments. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a conceptual diagram of an electromagnetic metamaterial-based hydrogen detection element. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a process for producing the hydrogen detection element according to the embodiment of the present invention. [Diagram 3] FIG. 3 is an image obtained by capturing a part of the pattern of the hydrogen storage metal film according to the embodiment of the present invention using an SEM. [Figure 4] FIG. 4 is a graph showing typical optical characteristics of a hydrogen detection element made of a dot-type electromagnetic metamaterial using simple palladium. [Diagram 5] FIG. 5 is a plan view of the hydrogen detection element according to the first embodiment. [Figure 6A] FIG. 6A is a graph showing the optical characteristics of the hydrogen detection element according to Example 1. [Figure 6B] FIG. 6B is a graph showing the optical characteristics of the hydrogen detection element according to Example 1. [Figure 7A] FIG. 7A is a graph showing the optical characteristics of the hydrogen detection element according to Example 2. [Figure 7B] FIG. 7B is a graph showing the optical characteristics of the hydrogen detection element according to Example 2. [Figure 8A] FIG. 8A is a graph showing the optical characteristics of the hydrogen detection element according to Example 3. [Figure 8B] FIG. 8B is a graph showing the optical characteristics of the hydrogen detection element according to Example 3. [Figure 9A] FIG. 9A is a graph showing the optical characteristics of the hydrogen detection element according to Example 4. [Figure 9B] FIG. 9B is a graph showing the optical characteristics of the hydrogen detection element according to Example 4. [Figure 10A] FIG. 10A is a graph showing the optical characteristics of the hydrogen detection element according to Example 5. [Figure 10B] FIG. 10B is a graph showing the optical characteristics of the hydrogen detection element according to Example 5. [Figure 11] FIG. 11 is a graph showing the simulation results of the transmittance when the thickness of a dot-type electromagnetic metamaterial made of Pd alone is changed. [Figure 12] FIG. 12 is a plan view of the hydrogen detection element according to the sixth embodiment. [Figure 13A] FIG. 13A is a graph showing the optical characteristics of the hydrogen detection element according to Example 6. [Figure 13B] FIG. 13B is a graph showing the optical characteristics of the hydrogen detection element according to Example 6. [Figure 14] FIG. 14 is a plan view of the hydrogen detection element according to the first modification. [Figure 15] FIG. 15 is a graph showing the optical characteristics of the hydrogen detection element according to the first modification. [Figure 16]FIG. 16 is a plan view of the hydrogen detection element according to the second modification. [Figure 17] FIG. 17 is a graph showing the optical characteristics of the hydrogen detection element according to the second modification. [Figure 18] FIG. 18 is a plan view of a hydrogen detection element according to the third modification. [Figure 19] FIG. 19 is a graph showing the optical characteristics of the hydrogen detection element according to the third modification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the present invention is not limited to the embodiment. In addition, in the description of the drawings, the same parts are denoted by the same reference numerals.
[0013] <Conventional example> As a conventional example, data showing the structure of the hydrogen detection element described in the examples of Patent Document 3 is shown in Table 1 (hereinafter, the first embodiment will be abbreviated to prior form 1, membrane body A of the second embodiment will be referred to as prior form 2A, and these may also be collectively referred to simply as prior forms, etc.). [Table 1]
[0014] It can be seen that the measurement wavelength of the prior art is approximately 3 to 6 μm from the position of the absorption peak wavelength of the infrared absorption spectrum shown in Figure 5 of Patent Document 3. Since a special spectroscope is required to perform measurement with detection light in this wavelength band, it is thought that the sensor itself will be expensive. In addition, among the preceding forms, the hydrogen absorption time (the time from the start of hydrogen supply until the shift in the absorption peak wavelength becomes saturated) is the longest for Precedent Form 1, which uses Pd alone, at about 2,400 s (40 minutes), while the shortest is about 15 s for Precedent Form 2E, which is in the 10 second range. However, Precedent Form 2E contains Au, a precious metal, in addition to Pd, which raises concerns about rising costs.
[0015] <Embodiment> Next, an embodiment of the present invention will be described. As shown in the previous example 1, the reason why the hydrogen absorption rate of palladium alone is slow is thought to be the slow rate of hydrogen movement inside palladium. Even when exposed to hydrogen for a few seconds, the surface of palladium absorbs hydrogen, but the inside remains pure palladium, and the overall proportion of hydrogen absorbed and its optical properties changed is small. Therefore, it takes time for the palladium inside to absorb hydrogen and change its properties.
[0016] Based on this, in the following embodiment, it is considered to promote hydrogen absorption by reducing the structure and pitch of the electromagnetic metamaterial and increasing the ratio of surface area to volume. As a result, the metastructure of the electromagnetic metamaterial produced in the embodiment is designed to be several hundred nm. Accordingly, the measurement wavelength of the electromagnetic wave can use the wavelength band from visible light to near infrared light (500 to 1,600 nm), making it possible to measure with an inexpensive spectrometer.
[0017] The structure of the embodiment will be described. The hydrogen detection element according to the embodiment of the present invention is formed into an electromagnetic metamaterial structure by periodically arranging hydrogen storage metals of a predetermined shape on a substrate at a predetermined pitch, and there are a dot type (first embodiment) in which a metastructure made of one metal film is periodically arranged at a predetermined pitch, and an ADB (Asymmetric-Double-Bar) type (second embodiment) in which a metastructure made of a combination of a plurality of mutually different metal films is periodically arranged at a predetermined pitch. Glass or the like can be used for the substrate. In addition, it is also possible to form an electromagnetic metamaterial structure by periodically arranging metastructures made of a hydrogen storage metal film formed on a substrate with holes of a predetermined shape at a predetermined pitch (hole dot type).
[0018] 2 is a schematic diagram showing an example of a process for producing a hydrogen detection element according to an embodiment of the present invention. A resist coat was formed on a substrate, a pattern was drawn by electron beam (EB) lithography, development was performed, a metal film was formed by EB deposition, and then lift-off was performed. 3A and 3B are images of a part of a pattern of a hydrogen storage metal film according to an embodiment of the present invention captured by a SEM (Scanning Electron Microscope). Fig. 3(a) is an image of a dot pattern, and (b) is an enlarged view thereof. Fig. 3(c) is an image of an ADB pattern, and (d) is an enlarged view thereof. The thickness of the hydrogen storage metal film can be measured by AFM (Atomic Force Microscopy), and the metal composition can be analyzed by EDX (Energy Dispersive X-ray Spectroscopy). The measurement data showing the structure of the examples (described later) measured in this way are shown in Table 2. [Table 2]
[0019] Next, the optical property evaluation of the embodiment will be described. Here, a representative example is shown in which hydrogen absorption time is fast and the change in spectrum is easy to understand. FIG. 4 is a graph showing typical optical properties when a hydrogen detection element of a dot-type electromagnetic metamaterial using simple palladium is measured using a microspectrometer. FIG. 4(a) is a graph showing how the absorption spectrum of the incident electromagnetic wave changes with the change in the hydrogen atmosphere. When hydrogen is injected into the electromagnetic metamaterial, it can be seen that the absorption spectrum changes from "under atmosphere" to "hydrogen being injected". After that, when the injection is stopped, it gradually changes from "10 seconds after hydrogen injection" to "30 seconds after hydrogen injection", and finally returns to the original absorption spectrum "under atmosphere". Then, with the change in the absorption spectrum, the absorption peak wavelength (sometimes called the bottom wavelength) also shifts, and when hydrogen is absorbed, it shifts to the long wavelength direction.
[0020] Figure 4(b) is a graph showing the change in bottom wavelength over time (minutes). The dot intervals in the graph are the time intervals (approximately 13 seconds) determined by the measuring device used, so in all three cases of hydrogen eruptions, the time it takes for the bottom wavelength to shift from the shortest wavelength (bottom wavelength α) to the longest wavelength (bottom wavelength β), i.e., the time it takes for hydrogen to be absorbed in an equilibrium reaction and to become saturated in the metal film (hydrogen absorption time), is less than 13 seconds. It can also be seen that the time it takes for the bottom wavelength to shift from the longest to the shortest, i.e., the time it takes for hydrogen absorbed in the metal film to be released in an equilibrium reaction and return to its original state (hydrogen release time), is about 20 seconds. It is not clear why the hydrogen release time appears to change in the three cases of hydrogen eruptions in Figure 4(b), but it is known that it gradually settles into a constant release time. Therefore, it was found that even a metamaterial made of palladium alone can absorb and release hydrogen within a few tens of seconds.
[0021] Figure 4(c) is a graph showing the time change in transmittance at the bottom wavelength (bottom wavelength α) in air, compared to Figure 4(b). Figure 4(c) shows that hydrogen can also be detected by the change in transmittance. Furthermore, it was confirmed that the time for the transmittance to shift from the minimum to the maximum value (hydrogen absorption time) was less than 13 seconds, similar to the shift in the bottom wavelength in Figure 4(b). In this way, the hydrogen detection element of the embodiment can bring about (control) changes in the reflection, transmission, or absorption spectrum of the incident electromagnetic wave in response to changes in the hydrogen atmosphere.
[0022] Table 3 shows the measurement data for the optical properties evaluation of the examples (described later). [Table 3]
[0023] First Embodiment An example of the hydrogen detection element according to the first embodiment having a dot-type electromagnetic material structure will be described below. Fig. 5 is a plan view of the hydrogen detection element according to the first embodiment. Example 1 A plan view of the hydrogen detection element according to Example 1 is shown in Fig. 5(a). Square (250 nm x 250 nm) hydrogen storage metal films 20 are periodically arranged at a pitch of 500 nm on a substrate 10. The measurement data showing the structure and the measurement data for evaluating the optical characteristics are shown in Tables 2 and 3, respectively. Figures 6A and 6B (collectively referred to as Figure 6, hereinafter) are graphs showing the optical characteristics of the hydrogen detection element according to Example 1. Graphs showing the optical characteristics similar to those in Figures 4(a) to (c) are shown in Figures 6(a) to (c). Furthermore, a graph comparing the absorption spectra in air and in hydrogen, obtained by actual measurement and simulation, is shown in Figure 6(d).
[0024] Example 2 A plan view of the hydrogen detection element according to Example 2 is shown in Fig. 5(b). Square (375 nm x 375 nm) hydrogen storage metal films 20 are periodically arranged at a pitch of 750 nm on a substrate 10. The measurement data showing the structure and the measurement data for evaluating the optical characteristics are shown in Tables 2 and 3, respectively. Fig. 7 is a graph showing the optical characteristics of the hydrogen detection element according to Example 2. Graphs showing the optical characteristics similar to those in Fig. 4(a) to (c) are shown in Fig. 7(a) to (c). Furthermore, a graph comparing the absorption spectra in air and in hydrogen, obtained by actual measurement and simulation, is shown in Fig. 7(d).
[0025] Example 3 A plan view of the hydrogen detection element according to Example 3 is shown in Fig. 5(c). Square (500 nm x 500 nm) hydrogen storage metal films 20 are periodically arranged on a substrate 10 with a pitch of 1,000 nm. The measurement data showing the structure and the measurement data for evaluating the optical characteristics are shown in Tables 2 and 3, respectively. Fig. 8 is a graph showing the optical characteristics of the hydrogen detection element according to Example 3. Graphs showing the optical characteristics similar to those in Fig. 4(a) to (c) are shown in Fig. 8(a) to (c). Furthermore, a graph comparing the absorption spectra in air and in hydrogen, obtained by actual measurement and simulation, is shown in Fig. 8(d).
[0026] Example 4 5(b) shows a plan view of the hydrogen detection element according to Example 4. The measurement data showing the structure and the measurement data for evaluating the optical characteristics are shown in Tables 2 and 3, respectively. As shown in Table 2, Example 4 differs from Example 2 in the thickness of Pd. Fig. 9 is a graph showing the optical characteristics of the hydrogen detection element according to Example 4. Graphs showing the optical characteristics similar to those in Fig. 4(a) to (c) are shown in Fig. 9(a) to (c). Furthermore, a graph comparing the absorption spectra in air and in hydrogen by actual measurement and simulation is shown in Fig. 9(d).
[0027] Example 5 5(b) shows a plan view of the hydrogen detection element according to Example 5. The measurement data showing the structure and the measurement data for evaluating the optical characteristics are shown in Tables 2 and 3, respectively. As shown in Table 2, Example 5 differs from Example 2 in that it contains Al. Fig. 10 is a graph showing the optical characteristics of the hydrogen detection element according to Example 5. Graphs showing the optical characteristics similar to those in Fig. 4(a) to (c) are shown in Fig. 10(a) to (c). Furthermore, a graph comparing the absorption spectra in air and in hydrogen, obtained by actual measurement and simulation, is shown in Fig. 10(d).
[0028] (Consideration) From Examples 1 to 4, it was confirmed that the electromagnetic metamaterial of this embodiment, even with Pd alone, achieves a short hydrogen absorption time of less than 13 seconds up to a pitch of 1,000 nm (sometimes referred to as a "fast (high) response speed"). Therefore, it is not necessary to add a precious metal to increase the response speed. In addition, since the bottom wavelength shows a red shift as the pitch increases, it is possible to design metamaterials to match any wavelength. Furthermore, as shown in Figures 6(d) to 9(d), the actual measurement results and the simulation results show roughly consistent changes, confirming the validity of the simulation model.
[0029] According to Example 5, even if Al is mixed into Pd, hydrogen detection can be performed in a short time, but compared to Example 2 and the like, it was found that Pd alone has a larger spectrum change (bottom wavelength change) and better performance (see Figures 7 and 10). Since Examples 2 and 5 have almost the same thickness, the difference is the presence or absence of aluminum in the metal film. By comparing these actual measurement results with the simulation results, it is possible to determine how much the shape and material composition deviate from the ideal electromagnetic metamaterial. According to Figure 10(d), the actual measurement result of the transmittance of Example 5 is higher than the simulation result, and has an overall smooth spectrum. In contrast, according to Figure 7(d), the actual measurement value of the transmittance of Example 2 is significantly lower and closer to the simulation result. Since the actual measurement result of Example 5 is thus significantly different from the simulation result, it is considered that Al is mixed into the metal film as an oxide, weakening the metallic properties of the material, which attenuates the Fano resonance. On the other hand, the hydrogen absorption and release time is short even with a mixture of Pd alone, Al, or alumina. From the above, it can be seen that the responsiveness and response speed to hydrogen are maintained even if the material is mixed with Al or alumina, but in order to obtain a spectrum with a higher Q value, it is more effective to use Pd alone.
[0030] Next, we will focus on the thickness of the hydrogen-absorbing metal film. Figure 11 is a graph showing the results of a simulation of the transmittance when the thickness of a Pd dot-type electromagnetic metamaterial is changed. Figure 11 shows that the material exhibits unique absorption up to a thickness of 9.0 μm, indicating that it has the properties of an electromagnetic metamaterial. Furthermore, at thicknesses of 1.0 μm or less, the bottom wavelength of the absorption spectrum appears, indicating that the material is suitable as a hydrogen detection element. Furthermore, referring to Example 2 (FIG. 7) and Example 4 (FIG. 9), the thickness of Example 2 is 89 nm, and the thickness of Example 5 is 182 nm, but they have the same structure, and both have short hydrogen absorption (less than 13 seconds) and release times (40 seconds). Therefore, it is considered that they will operate while maintaining a fast reaction speed to hydrogen at least up to a thickness of 182 nm.
[0031] <Second embodiment> An example of the hydrogen detection element according to the second embodiment having an ADB type electromagnetic material structure will be described below. Example 6 12 is a plan view of a hydrogen detection element according to Example 6. A combination of two rectangular hydrogen storage metal films 20 made of simple Pd particles with different dimensions (90 nm x 380 nm, 90 nm x 230 nm) is arranged in parallel on a substrate 10 to form a metastructure of an electromagnetic metamaterial, and the metastructures are periodically arranged with a pitch of 500 nm. The measurement data showing the structure and the measurement data for evaluating the optical characteristics are shown in Tables 2 and 3, respectively. Fig. 13 is a graph showing the optical characteristics of the hydrogen detection element according to Example 6. Graphs showing the optical characteristics similar to those in Fig. 4(a) to (c) are shown in Fig. 13(a) to (c). Furthermore, a graph comparing the absorption spectra in air and in hydrogen, obtained by actual measurement and simulation, is shown in Fig. 13(d).
[0032] (Consideration) From the optical characteristics in Figure 13, it can be seen that the transmission spectrum of the ADB-type electromagnetic metamaterial has a generally smooth shape, and the measured transmittance is generally higher than the simulation results. This is thought to be because the ADB structure is smaller than the Dot-type and is more prone to variation. On the other hand, the position and number of each absorption peak wavelength match the simulation results, and the direction of change in the absorption spectrum after hydrogen injection also matches the simulation results. Therefore, it has the properties to detect hydrogen, and the hydrogen absorption time is less than 13 seconds, and the release time is fast at 20 seconds, making it suitable for use in hydrogen detection.
[0033] <Modification> The modified examples are described below. Table 4 shows data showing the structure of the hydrogen detection element used as the modified example. [Table 4] As the shapes of the metal film of the dot-type electromagnetic material, a circle (variant 1) and a cross (variant 2) will be described.
[0034] 14 is a plan view of a hydrogen detection element according to Modification 1. On a substrate 10, circular hydrogen occluding metal films 20 (diameter 250 nm) are periodically arranged at a pitch of 500 nm. Fig. 15 is a graph showing the optical characteristics of the hydrogen detection element according to Modification 1. Fig. 15 shows the results of a transmission spectrum simulation in the case where circular metal films are periodically arranged, and a transition in the absorption peak wavelength is observed, from Pd: 770 nm in air to Pd: 780 nm in hydrogen, and a difference of about 10% is also observed in the transmittance.
[0035] 16 is a plan view of a hydrogen detection element according to Modification 2. On a substrate 10, cross-shaped (length 250 nm×width 125 nm) hydrogen occluding metal films 20 are periodically arranged at a pitch of 500 nm. Fig. 17 is a graph showing the optical characteristics of the hydrogen detection element according to Modification 2. Fig. 17 shows the results of a transmission spectrum simulation in the case where cross-shaped metal films are periodically arranged, and a shift in the absorption peak wavelength is observed (Pd in air: 800 nm, Pd in hydrogen: 830 nm), and a difference of about 10% is also observed in the transmittance. From the above, it is considered that the electromagnetic metamaterials according to the modified examples 1 and 2 can be used as hydrogen detection elements, and that the response speed can be improved based on the pitch value, etc. It is also expected that metal films of other shapes can be used.
[0036] The following describes a hole-dot type electromagnetic material in which the shape of the holes formed in the metal film is square (variation 3). 18 is a plan view of a hydrogen detection element according to Modification 3. A hydrogen storage metal film 20 is uniformly formed on a substrate 10, and square holes (375 nm×375 nm) are formed therein and periodically arranged with a pitch of 750 nm. Fig. 19 is a graph showing the optical characteristics of the hydrogen detection element according to Modification 3. Fig. 19 shows the simulation results of the transmission spectrum and reflection spectrum when square holes are periodically arranged in a Pd film, and there is a large difference between under air and under hydrogen, especially around 900 nm, with the transmission spectrum showing Pd under air: 940 nm and Pd under hydrogen: 970 nm, and the reflection spectrum showing Pd under air: 920 nm and Pd under hydrogen: 950 nm, indicating a shift in the absorption peak wavelength. From the above, it is considered that the electromagnetic metamaterial according to the modified example 3 can be used as an element for detecting hydrogen, and that the response speed can be improved depending on the pitch value, etc. It is also expected that other hole shapes can be used.
[0037] In this way, by creating an electromagnetic metamaterial that responds to visible light to near-infrared light using palladium alone or a mixture of palladium and aluminum, a hydrogen detection element has been developed that has a fast response speed to hydrogen of less than 13 seconds. Compared to prior art such as Patent Document 3, it can be seen that a faster response speed has been achieved without using precious metals. Furthermore, the visible to near-infrared wavelength band can be measured using an inexpensive spectrometer. It is possible to use electromagnetic waves of the order of magnitude larger than that of the dot type. It is possible to design a structure with a larger rate of change by devising the shape of the meta-structure of the electromagnetic metamaterial, such as the ADB type, in addition to the dot type.
[0038] Although the embodiments of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments, and various modifications are possible within the scope of the gist of the present invention. For example, the hydrogen storage metal is not limited to palladium, and other metals may be used. Metals other than Al may be blended. Furthermore, a hydrogen detection device can be provided by using the hydrogen detection element according to the present invention and providing a light source unit capable of emitting incident electromagnetic waves, a light receiving unit that receives light reflected or transmitted through the hydrogen detection element, and a detection unit that detects hydrogen based on the light receiving result of the light receiving unit.
[0039] The following are some possible embodiments of the present invention, but the present invention is not limited to these. (Aspect 1) An electromagnetic metamaterial in which metastructures of a specified shape and size made of a hydrogen-absorbing metal film are periodically arranged on a substrate at a specified pitch, the pitch being 1,000 nm or less, and which is a hydrogen detection element that controls the reflection, transmission, or absorption spectrum of incident electromagnetic waves. (Aspect 2) 2. The hydrogen detection element according to claim 1, wherein the hydrogen storage metal film does not contain a precious metal. (Aspect 3) 3. The hydrogen detection element according to aspect 2, wherein the hydrogen-storing metal film contains palladium. (Aspect 4) 4. The hydrogen detection element according to any one of aspects 1 to 3, wherein the incident electromagnetic wave has a spectrum ranging from visible light to near infrared light. (Aspect 5) 5. The hydrogen detection element according to any one of aspects 1 to 4, wherein the hydrogen occluding metal film has a thickness of 1.0 μm or less. (Aspect 6) 6. The hydrogen detection element according to any one of aspects 1 to 5, wherein the meta-structure is composed of a hydrogen-absorbing metal film having a square shape. (Aspect 7) 6. The hydrogen detection element according to any one of aspects 1 to 5, wherein the meta-structure is composed of a combination of hydrogen storage metal films having rectangular shapes of different sizes. (Aspect 8) A hydrogen detection device comprising: a hydrogen detection element according to any one of aspects 1 to 7; a light source unit capable of emitting the incident electromagnetic wave; a light receiving unit that receives light reflected by or transmitted through the hydrogen detection element; and a detection unit that detects hydrogen based on the light receiving result of the light receiving unit. [Explanation of symbols]
[0040] 10...substrate, 20...hydrogen storage metal film
Claims
1. An electromagnetic metamaterial in which metastructures of a predetermined shape and size made of a hydrogen-absorbing metal film are periodically arranged on a substrate at a predetermined pitch, the pitch being 1,000 nm or less, and which is a hydrogen detection element that controls the reflection, transmission, or absorption spectrum of incident electromagnetic waves.
2. 2. The hydrogen detection element according to claim 1, wherein said hydrogen occluding metal film does not contain a noble metal.
3. 3. The hydrogen detection element according to claim 2, wherein the hydrogen occluding metal film contains palladium.
4. 2. The hydrogen detection element according to claim 1, wherein the incident electromagnetic wave has a spectrum ranging from visible light to near infrared light.
5. 5. The hydrogen detection element according to claim 1, wherein the hydrogen occluding metal film has a thickness of 1.0 μm or less.
6. 5. The hydrogen detection element according to claim 1, wherein the meta-structure is composed of one square of the hydrogen-absorbing metal film.
7. 5. The hydrogen detection element according to claim 1, wherein the meta-structure is composed of a combination of rectangular hydrogen storage metal films of different sizes.
8. A hydrogen detection device comprising: a hydrogen detection element according to any one of claims 1 to 4; a light source unit capable of emitting the incident electromagnetic wave; a light receiving unit that receives light reflected by or transmitted through the hydrogen detection element; and a detection unit that detects hydrogen based on the light receiving result of the light receiving unit.
Citation Information
Patent Citations
Hydrogen sensor and its use
JP2005265590A
Hydrogen detection element, method of manufacturing hydrogen detection element, and hydrogen detection device
JP6775236B2
Surface plasmon resonance element for hydrogen detection, surface plasmon resonance-type optical hydrogen detector, and method for optically detecting hydrogen by using surface plasmon resonance
WO2011027899A1
Cited By
Membrane crack detection system, membrane crack detection method, and hydrogen purification apparatus
JP7829901B1